Prevotella histicola Transplantation Ameliorates Cognitive Impairment and Decreases Oxidative Stress in Vascular Dementia Rats - Rui Duan; Jiankang Hou; Xixi Wang; Zhihang Huang; Haiming Cao; Junya Hu; Qiang Peng; Huijie Duan; Qingguang Wang; Xiangliang Chen (Brain Sciences, 2023)
Vascular dementia is a type of dementia from brain damage caused by cerebrovascular lesions and vascular risk factors. Prevotella histicola is a species of Prevotella, belonging to the category of obligate anaerobe. The purpose of our work was to study the protection of Prevotella histicola on cognitive function in rats subjected to vascular dementia (VaD) and investigate underlying molecular mechanisms. The rats were randomly divided into three groups: control group, 2VO group and 2VO + Prevotella histicola group. The VaD rats (the 2VO group and 2VO + Prevotella histicola group) were generated by bilateral common carotid artery occlusion (2VO). Rats in the 2VO+ Prevotella histicola group were administered with Prevotella histicola twice daily. In comparison with the rats in the 2VO group, rats in the 2VO + Prevotella histicola group presented an enhanced cognitive ability, increased synapse-associated protein expression, a downregulation of proinflammatory factors and an upregulation of neurotrophic factors. The relevant mechanism of the protective effect of Prevotella histicola may be associated with the inhibition of glial cell-associated inflammation by regulating phosphorylation of CaMKII. In conclusion, Prevotella histicola attenuates neurological impairments via regulating synapse-associated protein expression and the liberation of inflammatory elements in vascular dementia rats. The findings above might benefit the development of Prevotella histicola transplantation as a promising treatment of VaD.